2012
DOI: 10.1093/her/cys098
|View full text |Cite
|
Sign up to set email alerts
|

Developing web-based training for public health practitioners: what can we learn from a review of five disciplines?

Abstract: During a time when governmental funding, resources and staff are decreasing and travel restrictions are increasing, attention to efficient methods of public health workforce training is essential. A literature review was conducted to inform the development and delivery of web-based trainings for public health practitioners. Literature was gathered and summarized from five disciplines: Information Technology, Health, Education, Business and Communications, following five research themes: benefits, barriers, ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 45 publications
1
55
0
2
Order By: Relevance
“…We found that the EBPH course is amenable to different formats, all of which have advantages and disadvantages for both organizers and participants (2,2427). Course organizers in our project reported moving to blended courses to address concerns about information overload, time away from work, and costs of training; their desire to reach broader audiences and people in remote locations led to development of distance courses.…”
Section: Summary and Implications For Practicementioning
confidence: 99%
“…We found that the EBPH course is amenable to different formats, all of which have advantages and disadvantages for both organizers and participants (2,2427). Course organizers in our project reported moving to blended courses to address concerns about information overload, time away from work, and costs of training; their desire to reach broader audiences and people in remote locations led to development of distance courses.…”
Section: Summary and Implications For Practicementioning
confidence: 99%
“…This approach offers several advantages to traditional instructional methods, including 24-hr accessibility, standardization of training, personalization/individualization (e.g., self-paced), widespread reach, risk free environment, and the opportunity for interactive exercises and multimedia components, which have been found to enhance knowledge retention [Ballew et al, 2013]. Web-based training is cost-effective and overcomes geographical, transportation, and child care constraints.…”
Section: Introductionmentioning
confidence: 99%
“…All 50 US states could use funding available from the Coordinated Chronic Disease Prevention and Health Program for chronic disease prevention training to expand EBPH training (31). Recent recommendations based on growing evidence point to web-based training as important for future efforts (32). Administrative evidence-based practices like expansion and tailoring of EBPH training and organizational support and policies for EBPH are needed to foster EBPH (33).…”
Section: Discussionmentioning
confidence: 99%